Brandon Carrell, MD (1911–1981). Issue 5 (3rd September 2021) - Holderread, Brendan; Rizkalla, James M.; Carpenter, Connor; Nimmons, Scott J. B.; Wilson, Philip; Ellis, Henry
Abstract: This biographical sketch on Dr. Brandon Carrell commemorates the life of an influential surgeon in the Dallas community. His contributions to pediatric orthopedic surgery helped form the field it is today.